Penatalaksanaan Fisioterapi pada Kasus Pneumothorax Dextra Et Causa Riwayat Tuberkulosis Paru dengan Pemasangan Water Sealed Drainage di Ruang Infeksi Rumah Sakit Paru Ario Wirawan Salatiga : Studi Kasus - Muhammad Raihan Maulidan; Dwi Rosella Komalasari; Ririt Eka Lestari (Lembaga Pengembangan Kinerja Dosen, 2025)
Human breathing involves a process that brings oxygen from the outside air to body tissues and expels carbon dioxide from the lungs. This mechanism is characterized by decreased inspiratory pressure, reduced minute ventilation, and increased tension in the respiratory muscles. So that breathing for humans is very important, in certain conditions, the respiratory tract can be disrupted and cause various symptoms, one of the respiratory disorders is pneumothorax. Pneumothorax is the presence of air in the pleural cavity. This can cause problems with ventilation, oxygen supply, or both. When these symptoms occur in the absence of lung trauma or obvious pathology, the patient is said to have primary spontaneous pneumothorax. If the pneumothorax is accompanied by complications or the presence of pulmonary disease, the prognosis of the disease will be worse and treatment will be more difficult. One of the actions in pneumothorax cases is physiotherapy rehabilitation. The purpose of this study is to find out whether physiotherapy intervention can reduce complaints in pneumothorax patients. . Patients are given exercise therapy in the form of pursed lip breathing, thoracic expansion exercise and gentle massage. From the therapy given as much as 3x therapy, the results were obtained in the form of decreased shortness of breath, increased thoracic expansion and increased functional activity.